FEATURES OF THE JOINT ACTIVITIES OF THE COMMISSION OF FORENSIC EXPERTS - Євсюков, Олександр (SWorldJournal, 2025)
The article is devoted to the analysis of the joint activities of the commission of forensic experts in the process of their execution of forensic expert research. The specificity of the activities of the commission of experts from a psychological point